Influences of forests on invertebrate communities in Icelandic streams - Medelyté, Gintaré, 1979- (2010)
Effects of forests on headwater stream invertebrate communities were studied in eastern and southern Iceland, which are two geologically different regions. The eastern research area is composed of solid basaltic rock with direct run-off streams. The streams drain treeless, birch and conifer forested catchments. The bedrock of the southern research area is porous hyaloclastite, and the streams are spring-fed. These streams drain two different types of catchments: barren land and birch forest. The density and taxonomic richness were similar among direct run-off streams within all three catchment types. In winter, different proportions of some taxa were found between streams draining treeless land and forests. Invertebrate assemblages were similar between birch and conifer forest streams. In summer, invertebrate densities were higher in the streams that had the greatest proportion of birch woodlands in their catchments, highest values of riparian biomass and greater algal biomass. In spring-fed streams, water temperature was the main factor explaining invertebrate densities and species composition, while presence of forest had no effect. Total densities and proportional abundances of taxa differed more between geographical locations than between catchment types. The younger bedrock influenced various habitat factors in the streams, such as availability of nutrients, water quality, temperature and primary productivity. Therefore, these factors were found to have a greater effect on invertebrate communities in Icelandic streams than forest presence or type. Environmental and Energy Research Fund of Orkuveita Reykjavíkur (UOOR), Centre for Advanced Forest Research on Ecosystem Services (CAR-ES) – Nordic/Baltic project, Agricultural Productivity Fund (Framleiðnisjóður landbúnaðarins), Energy Research Fund of Landsvirkjun (Orkurannsóknasjóður Landsvirkjunar), The Afforestation and Restoration Program Hekluskógar.